Influences of the Type of Fluxing Agent during Fluxcalcination of Kieselguhr on Formation of Crystalline Phases, Permeability and Colour - Schleicher, T.; Smejkal, Q.; Martin, A.; Russ, W.; Faulstich, M. (BrewingScience, 2009)
Commercial fluxcalcined kieselguhr or coarse kieselguhr is produced using sodium carbonate as fluxing agent. This coarse kieselguhr contains crystalline structures of silicon dioxide, mainly cristobalite and opal-CT. These crystalline structures are, in respirable form, classified as carcinogenic material and thereby cause concern in occupational health and disposal of spent material. In this paper the influence of the formation of crystalline material during fluxcalcination of kieselguhr using various fluxing agents is described. Additionally characteristics of the kieselguhr samples, concerning the suitability as filter aid have been investigated. Samples were heat treated from 900 °C to 1050 °C for 1h to 4h in a muffle kiln. These samples were analysed via X-ray diffractometry, in order to determine type and content of crystalline material. Based upon these experiments, it was proven that the fluxcalcination of kieselguhr can be accomplished using fluxing agents containing potassium ions. These fluxing agents lead to a coarse kieselguhr which is significantly lowered in crystalline matter, has suitable permeability and wet density and equal colour values compared to commercial fluxcalcined kieselguhr.